Design of Satellite Internet Defense System Based on Mobile Target Defense - XU Ruirong (天地一体化信息网络)
While satellite Internet promote information inter connectivity, they also raise increasingly complex security issues. This article introduced mobile target defense as proactive defense measure into the cyber protection of satellite Internet. By changing the IP address, protocol port information of satellite Internet pseudo-randomly, the system's resistance to interception attacks and denial of service attacks was enhanced, thereby achieving active defense. On this basis, a prototype system of satellite Internet based on mobile target defense was designed, which solved some key problems such as synchronization scheme, hopping data transmission, and verified the feasibility and effectiveness of the prototype system.